Early experience of transoral thyroidectomy: Comparison of robotic and endoscopic procedures. Issue 3 (6th December 2018) - Tae, Kyung; Lee, Dong Won; Song, Chang Myeon; Ji, Yong Bae; Park, Jung Hwan; Kim, Dong Sun; Tufano, Ralph P.
Abstract: Background: The aim of this study was to evaluate the feasibility, safety, and early surgical outcomes of transoral thyroidectomy and to compare robotic and endoscopic procedures. Methods: A total of 37 patients underwent robotic (23 cases) or endoscopic (14 cases) transoral thyroidectomy. We compared the outcomes of the two procedures. Results: Of the 37 patients, 2 were converted to the robotic facelift approach as a result of an intraoperative CO2 embolism and inability to remove the tumor. The mean operative time was 172.8 ± 37.5 minutes. Transient recurrent laryngeal nerve palsy occurred in one case, and transient hypoparathyroidism in two cases. Most of patients were satisfied with the postoperative cosmesis. There were no significant differences between the robotic and endoscopic procedures, except for operative time, which was significantly longer in the robotic group. Conclusion: Robotic and endoscopic transoral thyroidectomies are both feasible and safe in appropriate patients.